The Business and Marketing Environment - Palmer Adrian; Worthington Ian (Mcgraw Hill Book Company, 1992)
A multi-disciplinary examination of the factors which affect vital management and marketing decisions. Preface, Marketing: An Overview, Classification of Business Organizations, Organizational Growth, The Internal Environment, The Microeconomic Environment, The Macroeconomic Environment, The International Marketing Environment, The Political Environment, The Demographic Environment, The Social and Cultural Environment, The Technological Environment, The Legal Environment, Analyzing the Marketing Environment, Index.